Menachem Kellner: Jewish universalism - Hughes, Aaron W.; Tirosh-Samuelson, Hava (Library of contemporary Jewish philosophers, 2015)
Heresy and the nature of faith in Medieval Jewish philosophy / Menachem M. Kellner -- Maimonides on the science of the Mishneh Torah: provisional or permanent? / Menachem M. Kellner -- Maimonides' "True religion": for Jews or all humanity? / Menachem M. Kellner -- We are not alone / Menachem M. Kellner -- Interview with Menachem M. Kellner / Hava Tirosh-Samuelson